Crowded Housing and Urban Residence as Risk Factors for Under-Five Children’s Pneumonia in Indonesia: Analysis of SSGI 2024 Data - Fadilah Yuma Zahara; Defriman Djafri; Aria Gusti (Jurnal Keselamatan Kesehatan Kerja dan Lingkungan, 2026)
Pneumonia remains the leading cause of morbidity and mortality among under-five children in Indonesia, with cases tending to increase each year. This study aimed to examine the association between crowded housing, cooking fuel type, nutritional status, sex, and classification of residence with the incidence of under-five children in Indonesia. This study used a cross-sectional design with secondary data from the 2024 Indonesian Nutritional Status Survey. The sample included 201,017 children aged 12-59 months. Bivariate analysis was performed using the chi-square test. The bivariate analysis of five variables showed that crowded housing (p=0.008; POR=1.273) and urban residence (p<0.001; POR=1.918) were significant risk factors for under-five children’s pneumonia. Meanwhile, sex (p=0.412), nutritional status (p=0.216), and cooking fuel type (p=0.290) did not show statistically significant associations. Crowded housing conditions and living in urban areas are significant risk factors for pneumonia in children under five in Indonesia. Public health interventions should prioritize improving household ventilation, reducing indoor crowding, and developing targeted pneumonia prevention programs in urban areas.